Digital Literacy as a Media for Da'wah Communication in Overcoming Disaster Hoaxes in Cianjur Regency - Andriani, Astri Dwi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
Disaster hoaxes often emerge after a disaster occurs, especially in vulnerable areas such as Cianjur. Digital literacy has great potential as a da'wah tool to provide education to the public so that they do not easily believe in false information. This article discusses the importance of digital literacy in da'wah to ward off disaster hoaxes, by adding Islamic communication ethical values such as Sad sayings, the words of the cover, Qaulan layyinan, Qaulan Kariman, qaulan balighan, And qaulan maysuran. The aim of this research is to present data on how the people of Cianjur carry out digital literacy as a medium for da'wah in preventing disaster hoaxes in Cianjur Regency. This research uses a constructivist paradigm with a qualitative research type. The method used is a descriptive case study, the theory used is social construction theory. The research results show that there are at least 4 digital literacy movements to overcome disaster hoaxes in Cianjur Regency, namely: 1) Cianjur Saber Hoaks (a digital literacy movement that clarifies content suspected of being a hoax circulating on the internet); 2) Tanjeur Cianjur (disaster management and digital literacy movement carried out online and offline); 3) UNPI & Jayabaya Psychosocial Support and creation of a guidebook for volunteers in providing psychosocial support; and 4) Asean Digital Literacy Program (socialization of the dangers of hoaxes and the ITE Law). The implications of this research are 1) Provide descriptive knowledge regarding the online communication climate in Cianjur Regency after the earthquake; 2) Enriching the body of knowledge in the field of digital literacy; and 3) can be used as a reference and guide for volunteers in fighting disaster hoaxes.